THE RIFAMPICIN RED FLAG - Matthews, Joel; Matthews, Gerard Jason; Merican, Nor Shaffinaz Yusoff Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Rifampicin is an essential first-line anti-tuberculosis (TB) drug which exhibits potent hepatic enzyme-inducing properties. It has significant drug interactions with an array of other medications, including hydrocortisone as we report in this case. CASE A 65-year-old male, HIV positive, treatment-naive, with concurrent primary adrenal insufficiency (Synacten done: Cortisol 0 hour 247.8 nmol/L, 60 minutes 316 nmol/L, and normal ACTH 7.76 pmol/L) on hydrocortisone 10 mg/5 mg replacement for 4 months was admitted for prolonged fever and lethargy. He was diagnosed to have extrapulmonary TB by urine lipoarabinomannan (LAM) test and was started on isoniazid, rifampicin, pyrazinamide plus ethambutol – HREZ regime. On Day 12 of HREZ, he exhibited hypoglycaemia, postural hypotension, and hyponatremia. Serial monitoring of his sodium levels showed a decreasing trend from a normal level initially of 135 mmol/L to a nadir of 116 mmol/L on day 21 of rifampicin. A diagnosis of adrenal insufficiency secondary to rifampicin was made. Rifampicin accelerates cortisol metabolism resulting in low levels of serum cortisol. The patient was started on IV hydrocortisone 50 mg QID. He responded well to treatment with amelioration of symptoms and normalization of sodium levels. Steroids were then tapered to oral hydrocortisone with the lowest replacement dose of 20 mg/10 mg daily (double the usual physiological dose) given the ongoing use of rifampicin. The patient was started on hydrocortisone tablet 20/10 mg daily and with no further dose reduction planned while concurrently on rifampicin. The hydrocortisone dosage will be gradually reduced to the standard physiological dose upon the patient’s completion of rifampicin treatment. CONCLUSION Prompt identification of drugs that can affect cortisol metabolism is essential to for patients on hydrocortisone replacement therapy. Close monitoring, multidisciplinary collaboration, personalized dose adjustments and careful tapering of hydrocortisone with biochemical and clinical correlation are paramount in navigating the challenges posed by rifampicin-hydrocortisone interaction.